Surgical technique in stapedotomy hearing outcome and complications. (20th May 2019) - Pauli, Nina; Strömbäck, Karin; Lundman, Lars; Dahlin‐Redfors, Ylva
Abstract : Objectives/Hypothesis: The aim of this study was to investigate different stapes surgery techniques in relation to hearing outcome and risk for complications such as tinnitus, hearing deterioration, dizziness, and taste disturbance. Study Design: Retrospective database review. Methods: The study was based on data from the Swedish Quality Register for Otosclerosis Surgery (SQOS). Two study protocols were completed by the surgeon, and a questionnaire was distributed to each patient 1 year after surgery. A total of 832 patients operated on during 2013 to 2016 were included. Pure‐tone audiometry was performed preoperatively and 1 year after surgery. Results: There was no significant difference in postoperative high‐frequency hearing thresholds among the subgroups at the 1‐year follow‐up. The CO2 + drill laser group had the best hearing outcome according to the following criteria: air‐bone gap closure ≤10 dB, air‐conduction improvement >20 dB, and bone conduction not worsened >5 dB. The overall complication rate was low in all analyzed groups. The most commonly reported symptom after surgery was newly developed or worsened tinnitus (6%). Subjective hearing 1 year after surgery was reported to be better or much better in 91% of the patients. Conclusions: The combination of a drill and CO2 laser or a drill and potassium‐titanyl‐phosphate laser resulted in the best hearing outcome in this study from the SQOS. There were no major differences in high‐frequency hearing outcome when comparing the different surgical techniques. Complications from surgery were rare, and patient satisfaction was very high 1 year after the operation. Level of Evidence: NA Laryngoscope, 130:790–796, 2020